Role of Nb on the phase stability and morphology of Ti–Ni–Cu–Nb alloys - Jessica Dornelas Silva; Gisele Fernandes Chaves Macieira; Dilson Silva dos Santos; Leandro de Arruda Santos; Vicente Tadeu Lopes Buono (Journal of Materials Research and Technology, 2022)
Ti52-xNi38Cu10Nbx alloys with Nb additions of x = 4, 6, and 10 at.% were produced through arc melting. The phase constitution and morphology were evaluated through X-ray diffraction, microstructural analyses (scanning electron microscopy/energy-dispersive X-ray spectroscopy), and thermodynamic calculations (ThermoCalc). The as-cast alloys exhibited a TiNi matrix, β-Nb/TiNi eutectic, and Ti2Ni precipitates. Under equilibrium conditions, TiNi and a small fraction of β-Nb were expected. Increasing the Nb content resulted in a higher β-Nb volume fraction, development of different morphologies for Ti2Ni precipitates, and formation of Ti particles. The Scheil calculator and virtual composition of the liquid were used to simulate the effect of chemical segregation during solidification. We demonstrated that the metastable phases formed during solidification and the Nb content played a vital role in the solidification sequence, phase distribution, and morphology of the alloy.